Pengaruh Media Animasi Terhadap Hasil Belajar Peserta Didik Pada Materi Perubahan Cuaca - Sinaga, Mia Endang Sari; Limbong, Winny Sunfriska; Halawa, Setiani (Pusdikra-Publishing.com, 2024)
The research aims to know the effect of animation media on science learning outcomes on weather change material using animation media and conventional methods on third grade students of UPT SDN 066049 Medan Helvetia. This type of research is quantitative with a quasi-experimental method. The population in this study was all thrid grade with a total of 32 students. The sample used was the total sampling method. Data collection techniques in this study were carried out through tests, observations, and documentation. Data analysis using the t-test. Based on the t-test table, it is known that sig (2-tailed) for the pretest and posttest values ????is 0.002 <0.05 then ho is accepted and ha is rejected. So it can be concluded that there is an influence of third animation media on science learning outcomes on weather change material for third grade UPT SDN 066049 Medan Helvetia.